Plasma Electrolytic Oxidation (PEO) Coating on γ-TiAl Alloy: Investigation of Bioactivity and Corrosion Behavior in Simulated Body Fluid - Fatemeh Salahshouri; Ehsan Saebnoori; Sina Borghei; Majid Mossahebi-Mohammadi; Hamid Reza Bakhsheshi-Rad; Filippo Berto (Metals, 2022)
The effect of applied voltage (400, 450, and 500 V) on the microstructure, bioactivity, and corrosion rate of plasma electrolytic oxidation (PEO) coatings on γ-TiAl alloy was investigated. The microstructure and chemical composition of the achieved coatings were studied, along with their corrosion and bioactivity behaviors in simulated body fluid (SBF). The results demonstrated that the higher the coating′s surface pore, the greater the number of suitable sites for the formation of hydroxyapatite with a spherical structure. The coatings applied utilizing 400, 450, and 500 V displayed 59.4, 96.6, and 145 Ω.cm2 as their inner layer electrical resistances, respectively. The findings of the biological examination revealed that Mesenchymal stem cells (MSCs) displayed more cytocompatibility and had a higher capacity for cell attachment in the PEO-coated sample than in γ-TiAl, as a result of better initial cell attachment made possible by the topography of the 500 V PEO coatings. The latter has significant potential to be employed in orthopedic applications.